Effect of Different Feed Starters on the Physical Quality, Moisture Content, and pH of Corn Stover (Zea mays) Silage - Ezra Pradana, Alieffito; Rahayu, Novia; Ardigurnita, Firgian (Bulletin of Applied Animal Research, 2026)
Balancing nutrient requirements with feed availability is a major challenge in livestock production systems. To address this issue, feed preservation technologies such as silage are needed to maintain feed quality and ensure continuous supply throughout the year. Corn stover is a potential raw material for silage production due to its abundance, but it has a limitation in its relatively low content of water-soluble carbohydrates (WSC), which often leads to suboptimal fermentation. One strategy to improve the fermentation process is the addition of fermentable carbohydrate sources such as pollard and rice bran (bekatul). This study aimed to evaluate the effect of adding pollard and rice bran on the physical quality (color, aroma, texture), moisture content, and pH of corn stover silage, as well as to determine the most effective type and inclusion level. The experiment was conducted using a Completely Randomized Design (CRD) single factor with seven treatments: P0 (control), P1 (pollard 3%), P2 (pollard 5%), P3 (pollard 7%), P4 (rice bran 3%), P5 (rice bran 5%), and P6 (rice bran 7%). Each treatment was replicated four times, resulting in 28 experimental units, with each unit consisting of 10 kg of corn stover silage. The results showed that the addition of pollard and rice bran significantly affected the pH and odor of silage (P<0.05), but had no significant effect on color, texture, or moisture content (P>0.05). Treatments P3 (pollard 7%) and P4 (rice bran 3%) produced the lowest pH (6.50) and the most preferred aroma, although the values did not reach the ideal range of high-quality silage (3.8–4.2). Therefore, 7% pollard can be recommended as the most effective additive to improve the fermentation quality of corn stover silage. Keywords: Corn stover, pH, Pollard, Rice Bran, Silage.